Aortic stiffness is not only associated with structural but also functional parameters of retinal microcirculation - Dąbrowska, Edyta; Harazny, Joanna M.; Miszkowska-Nagórna, Eliza; Stefański, Adrian; Graff, Beata; Kunicka, Katarzyna; Świerblewska, Ewa; Rojek, Agnieszka; Szyndler, Anna; Gąsecki, Dariusz; Wolf, Jacek; Gruchała, Marcin; et al. (Microvascular Research, 2020)
Objective: The aim of the study was to test the hypothesis that alterations in large arteries are associated with microvascular remodelling and decreased retinal capillary blood flow. Methods: The study group comprised of 88 patients with essential hypertension and 32 healthy controls. Retinal microcirculation was evaluated by scanning laser Doppler flowmetry. Macrovascular changes were assessed on the basis of arterial stiffness measurement (carotid-femoral pulse wave velocity), its hemodynamic consequences (central pulse pressure, augmentation pressure, augmentation index) and intima media thickness of common carotid artery. Results: Pulse wave velocity was inversely correlated to mean retinal capillary blood flow in hypertensive patients (R = −0.32, p < 0.01). This relationship remained significant in multivariate regression analysis after adjustment for age, sex, central systolic blood pressure (BP) and body mass index (β = −31.27, p < 0.001). Lumen diameter (LD) of retinal arterioles was significantly smaller in hypertensive then normotensive subjects (79.4 vs. 83.8, p = 0.03). Central and brachial systolic, diastolic and mean BPs were significantly correlated with LD and outer diameter of retinal arterioles. The relationship between LD and central BPs remained significant in multivariate analysis (β = −0.15, p = 0.03 for cSBP; β = −0.22, p = 0.04 for cDBP; β = −0.21, p = 0.03 for cMBP). Moreover, in a subgroup with cardiac damage central and brachial pulse pressure were positively associated with retinal wall thickness, wall cross sectional area, and wall to lumen ratio. Conclusion: In conclusion, the study provides a strong evidence that microcirculation is coupled with macrocirculation not only in terms of structural but also functional parameters.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Aortic stiffness; Microcirculation; Pulse wave velocity; Scanning laser Doppler flowmetry